Kirke, kulturarv og konflikt – Mårup på klinten - Wienberg, Jes (Hikuin, 2006)
Church, Heritage and Conflict – Mårup on the cliff By Jes Wienberg The medieval church of Mårup in Jutland, Denmark, is situated on a cliff only a few meters from the North Sea. Every year the sea comes closer. The church is deserted since 1928. As the erosion of the cliff accelerated in the 1980s a vigorous debate started regarding the future of the church and its churchyard. The church has become a great tourist attraction as a symbol of cultural and human perishability in front of the relentless nature. Different alternatives have been considered: Preservation by coast protection, movement futher into land, transfer to an open air museum or investigation before destruction. The local population organised in a society »The Friends of the Church of Mårup« wants coastal protection, wheras the antiquarian authorities already have carried out archaeological investigations and documentation before a planned taking down of the building. The locals want to preserve the church unchanged as a symbol of the coastal population in Jutland, wheras the authorities view the church primarily as a source material. The authorities give priority to the protection of the environment with its eroding cliff. The debate is seen in perspective of the general transformation of churces into cultural heritage. The gradual change around 1900 from ruthless renewal and demolition of medieval churches, to voluntary or legal protection is followed in Denmark and Scania (Sweden). Since 1918 no medieval church has been deliberately demolished in these areas. Finally, the debate of Mårup is seen in the perspective of international conflicts concerning the interpretation, use and ownership of cultural heritage.